PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT BANK RAKYAT INDONESIA (PERSERO) TBK JAKARTA PUSAT - Sulistio, Raditio; Ramadhon Pratama, Rizky; Hadjrillah , Tjeri (YBAMB, 2024)
The purpose of this study was to determine of Motivation and Work Stress on the Performance of Branch Office Employees of the Region III Education Service, West Java Province. The method used is quantitative. The sampling technique used saturated samples and a sample of 60 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis tests (t test and f test). Based on the research results of the hypothesis test (t test) of the motivation variable (X1) on employee performance (Y), the calculated t value > t table or (3.464 > 2.001) is confirmed. This is reinforced by the significance value < 0.050 or (0.000 < 0.050). Thus, Ho is rejected. H1 is accepted, this shows that there is a significant influence between work safety and employee performance. Hypothesis Test Results (t Test) Job Stress Variable (X2) on Employee Performance (Y) Based on the research results, the calculated t value > t table or (7.098 > 2.001). This is also reinforced by a significance value < 0.050 or (0.000 < 0.050). Thus Ho is rejected and H2 is accepted, this shows that there is a significant influence between Work Discipline on Employee Performance. Results of Simultaneous Hypothesis Testing (F Test) Motivation (X1) and Job Stress (X2) on Employee Performance (Y) Based on the research results, the calculated F value > F table (26.636 > 3.16) is obtained, this is also confirmed by the significance < 0.050 or (0.000 < 0.050). Thus, Ho is rejected. H3 is accepted, this shows that there is a significant simultaneous influence between Motivation and Work Stress on Employee Performance.